Illiberal Populism as a Polarizing Factor of Regional Cooperation in Central Europe - Ladislav Cabada (Revista UNISCI, 2024)
Central European identity and regionality are very traditional and deeply rooted discourses. Over the past 35 years, a number of regional cooperation formats have emerged, among which the Visegrad Group has acquired a special position. This weakly institutionalised and thematically selective regional organisation has nevertheless established itself in the last 15 years as one of the visible actors of so-called populist regionalism. The (partial) transformation of the V4 towards populist foreign policy, national conservatism and Euroscepticism is the subject of our analysis. Using the concepts of populist regionalism and illiberal populism, it focuses on the formation of a monolithic discourse of the V4 as a group opposed to the international liberal order and the "Brussels agenda" in terms of values and public policies. We also examine the negative implications of this populist appropriation of the V4 for the region's position within the EU.